2016
DOI: 10.1128/aem.00695-16
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Probiotics Inhibits Absorption of the Heavy Metal Cadmium by Protecting the Intestinal Barrier

Abstract: The heavy metal cadmium (Cd) is an environmental pollutant that causes adverse health effects in humans and animals. Our previous work demonstrated that oral administration of probiotics can significantly inhibit Cd absorption in the intestines of mice, but further evidence is needed to gain insights into the related protection mode. The goal of this study was to evaluate whether probiotics can inhibit Cd absorption through routes other than the Cd binding, with a focus on gut barrier protection. In the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(113 citation statements)
references
References 51 publications
7
106
0
Order By: Relevance
“…Moreover, pro-inflammatory cytokines can activate the NF-kB pathway, which has been identified to be critical to oxidative stress, and then generate reactive oxygen species (ROS) [44]. At the same time, the production of ROS will aggravate the inflammatory process [11]. Oxidative stress may result in loss of tight junction integrity and increased paracellular permeability [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pro-inflammatory cytokines can activate the NF-kB pathway, which has been identified to be critical to oxidative stress, and then generate reactive oxygen species (ROS) [44]. At the same time, the production of ROS will aggravate the inflammatory process [11]. Oxidative stress may result in loss of tight junction integrity and increased paracellular permeability [45].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics exhibit a variety of health-promoting functions [10] and there is accumulating evidence that some probiotics have the potential to alleviate metal toxicity [11,12]. Moreover, probiotics can provide benefits to the host gut through a diverse set of mechanisms that include modulation of immune responses, alleviation of oxidative stress and reduce intestinal permeability by maintenance of intestinal barrier integrity by expression and distribution of TJ proteins [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal toxicity of Cd includes disruption of intercellular junctions, paracellular leakage, and inflammation . More recently, Cd has also been shown to modify gut immunity and the gut microbiota which could have clinical impact in the context of immune diseases such as inflammatory bowel disease . Clearly, a better understanding of the impact that chronic exposure to low levels of Cd may have on the intestinal integrity and function is of primary importance.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have also demonstrated that the beneficial effects of lactobacilli in alleviating the toxic effects of metals probably involve additional mechanisms beyond the sequestering of metals at the intestinal lumen. These include protection against oxidative stress and enhancement of the intestinal barrier function, leading to a decreased permeability to metals . Current knowledge of the capacity of LAB in protecting humans from metal toxicity is quite limited: a single clinical trial has been carried out in children and pregnant women in an at‐risk population.…”
Section: Introductionmentioning
confidence: 92%
“…Besides the in vitro binding of heavy metals in aqueous solutions, proof of concept experiments have established the efficacy of lactobacilli not only in the removal of Cd in situ from contaminated foods such as fruit juices, but also in in vivo animal trials. For example, Lactobacillus plantarum strains that possess high capacity of Pb, Cd and Cu binding have been assayed in mice . In this model, a reduction in metal tissue accumulation and increased metal fecal excretion has been observed in animals suffering metal chronic exposure through drinking water.…”
Section: Introductionmentioning
confidence: 99%